Nano silicon dioxide loaded ruthenium-copper bimetallic catalyst and preparation and application thereof
Through nano-silicon dioxide-supported ruthenium copper bimetallic catalyst, the strong dissociation of activated hydrogen and copper cluster form of ruthenium is used to coordinate the catalyzing of acetylene hydrogenation, which solves the problems of low utilization rate of precious metals and high reaction temperature of existing catalysts, and achieves the problem of low concentration of precious metals and high reaction temperature. Selective hydrogenation of low-temperature and high-efficiency acetylene is improved, and the selectivity and stability of the catalyst are improved.
Patent Information
- Application Number
- CN202411549666.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
AI Technical Summary
The existing acetylene selective hydrogenation catalysts have problems in the ethylene industry with low utilization of precious metals, high by-product generation, and high reaction temperature, resulting in poor stability, which limits the efficient catalytic performance of copper-based catalysts at low temperatures.
Using nano-silica-supported ruthenium copper bimetallic catalyst, the catalytic dissociation and activation ability of the catalyst is improved by introducing ruthenium to strongly dissociate activated hydrogen, and exists through the cluster form of copper to increase beneficial catalytic active sites and coordinate the catalytic addition of acetylene Hydrogen reduces the complete conversion temperature of acetylene and reduces the generation of coupling by-products.
Highly efficient catalytic selective hydrogenation of acetylene at low temperatures is achieved, which improves the selectivity and stability of the catalyst, reduces the metal load, reduces the reaction temperature, and significantly improves the performance and economicality of the catalyst.
Smart Images

Figure HDA0005114728460000011 
Figure HDA0005114728460000012 
Figure HDA0005114728460000013
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of acetylene hydrogenation reaction catalysts, and specifically relates to a nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] Ethylene (C2H4) is a basic chemical raw material that can be used to produce plastics, fibers, rubber and other chemicals, and has very important industrial application value. In the ethylene industry, the presence of a small amount of acetylene impurities in the ethylene feed gas will not only poison the catalyst of the downstream polymerization reaction, but also lead to a decrease in the production quality of polymer products. Catalytic selective hydrogenation of acetylene to ethylene is a key link in achieving efficient purification of ethylene feed gas, and is of great significance in the ethylene industrial production process.
[0003] The traditional acetylene selective hydrogenation catalyst widely used in the ethylene industry is a palladium-silver catalyst supported on alumina. However, this catalyst has low ethylene selectivity, high production of byproduct green oil, and low utilization of precious metal atoms. As the price of precious metals rises year by year, the catalyst cost increases significantly. The expensive price and scarcity of precious metals make it of great significance to design and develop low-cost and efficient non-precious metal acetylene hydrogenation catalysts as economical and efficient alternatives to palladium-based catalysts. Copper-based catalysts show good ethylene selectivity for acetylene hydrogenation, but their weak catalytic hydrogenation activity requires an increase in reaction temperature to achieve the reaction requirements. Most catalysts with copper as the active metal must achieve complete conversion of acetylene at 200°C. However, the catalytic hydrogenation of acetylene is an exothermic reaction. The higher reaction temperature will cause it to face problems such as polymerization coupling side reactions and poor stability. This makes it impossible to give full play to the high selectivity advantage of copper in the selective hydrogenation of acetylene, limiting the low-temperature and efficient selective hydrogenation of acetylene by Cu-based catalysts. Summary of the invention
[0004] To solve the above problems, the purpose of the present invention is to provide a nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst and its preparation method and application, and to construct an atomic-level dispersed ruthenium-copper bimetallic acetylene hydrogenation catalyst by introducing metal ruthenium with strong dissociation ability for hydrogen. A small amount of the second component metal ruthenium is added to improve the ability of the catalyst to dissociate activated hydrogen, increase the number of beneficial catalytic active sites, and at the same time, copper exists in the form of clusters, overcoming the disadvantages of competitive adsorption of reactants on isolated metal active sites. The two metals synergistically catalyze acetylene hydrogenation, improve catalytic performance, reduce the temperature for complete conversion of acetylene, and the low reaction temperature helps to reduce the generation of coupling by-products, further improve the selectivity and stability of the catalyst, and realize the non-precious metal copper at low temperature. Efficient catalysis of acetylene selective hydrogenation. In addition, from the perspective of maximizing the utilization rate of metal atoms, low metal loading and high catalytic activity are achieved, providing new ideas for the design and development of new low-cost, high-activity, high-selectivity atomic-level dispersed non-precious metal catalysts suitable for acetylene selective hydrogenation reactions.
[0005] To achieve the above purpose, the technical solution of the present invention is as follows:
[0006] A nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst, the catalyst uses nano-silicon dioxide as a carrier, the average particle size is 20nm; copper and ruthenium are used as active materials, copper is dispersed and anchored on the carrier surface in the form of clusters and ruthenium is dispersed and anchored in the form of single atoms. The copper loading in the catalyst is 0.1wt.% to 2wt.% of the carrier mass, preferably 0.25wt.% to 1wt.%; the ruthenium loading is 0.02wt.% to 0.5wt.% of the carrier mass, preferably 0.05wt.% to 0.2wt.%.
[0007] During the acetylene hydrogenation reaction, when the reaction temperature exceeds 170° C., the acetylene conversion rate of the catalyst reaches 100%, and the ethylene selectivity is 90%-100%.
[0008] The preparation method of the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst comprises the following steps:
[0009] Step 1. Preparation of nano-silica supported copper catalyst precursor by strong electrostatic adsorption method
[0010] The preparation process of nano-silica supported copper catalyst precursor is as follows: weighing Cu precursor and dissolving it in ammonia solution to obtain a mixed solution; adding nano-silica carrier to the mixed solution, stirring at room temperature to react, and then filtering, washing, and vacuum drying to obtain nano-silica supported copper catalyst precursor; wherein the molar ratio of NH3 to Cu in the mixed solution is n(NH3):n(Cu)>(20:1); the Cu precursor is copper nitrate; the average particle size of nano-silica is 20nm, and the mass ratio of carrier to copper is (50-1000):1; the reaction time is 2h-12h, the stirring rate is 300r / min-900r / min; the drying temperature is 60℃-80℃;
[0011] Step 2. Preparation of nano-silica-supported ruthenium-copper bimetallic catalyst precursor by strong electrostatic adsorption method
[0012] The preparation process of nano-silica supported ruthenium copper bimetallic catalyst precursor is as follows: weighing Ru precursor and dissolving it in ammonia solution to obtain a mixed solution; adding nano-silica supported copper catalyst precursor to the mixed solution, stirring at room temperature, filtering, washing, and vacuum drying to obtain nano-silica supported ruthenium copper bimetallic catalyst precursor; wherein the Ru precursor is hexaammineruthenium chloride; the molar ratio of NH3 and Ru in the mixed solution is n(NH3):n(Ru)>(20:1); the mass ratio of the added amount of nano-silica supported copper catalyst precursor to Ru is (200-5000):1; the stirring time is 2h-12h, the stirring rate is 300r / min-900r / min; the drying temperature is 60℃-80℃;
[0013] Step 3. Preparation of nano-silica supported ruthenium-copper bimetallic catalyst by reduction treatment
[0014] The nano-silica-supported ruthenium-copper bimetallic catalyst precursor is reduced in a hydrogen-helium mixed atmosphere to obtain a nano-silica-supported ruthenium-copper bimetallic catalyst; wherein the hydrogen gas volume fraction in the hydrogen-helium mixed atmosphere is 10 vol.%-100 vol.%, the flow rate is 20 mL / min-100 mL / min; the reduction temperature is 250° C.-350° C., and the reduction time is 0.5 h-2 h.
[0015] The nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst is used in the acetylene hydrogenation reaction to catalyze the selective hydrogenation of acetylene in the mixed raw gas to generate ethylene;
[0016] The composition of the mixed raw gas is calculated by volume fraction: acetylene 0.5vol.%-1vol.%, hydrogen 5vol.%-10vol.%, ethylene 10vol.%-20vol.%, helium as the balance gas; the space velocity is 2000-60000mL·g -1 ·h -1 .
[0017] The invention adopts a strong electrostatic adsorption method, uses nano-silicon dioxide as a carrier, adjusts the pH of the solution to be higher than the isoelectric point of the carrier by adjusting ammonia water, and makes the carrier negatively charged; Cu and Ru respectively form positively charged metal complexes in the ammonia water, and the metal is anchored on the surface of the carrier by strong electrostatic adsorption, so as to prepare an atomic-level dispersed ruthenium copper bimetallic catalyst for acetylene selective hydrogenation reaction. The preparation method of the invention is simple, the interaction between the metal and the carrier is strong, the metal is stably anchored on the surface of the carrier, and the metal can be completely adsorbed, without causing waste of metal.
[0018] In the RuCu / SiO2 catalyst of the present invention, copper is dispersed on the carrier in the form of fully exposed clusters, the metal particles are small in size, the active sites are fully exposed, and the metal atom utilization rate is high compared to metal particle catalysts. In addition, the cluster catalyst has abundant active sites, and the increase of beneficial catalytic active sites solves the problem of low catalytic activity caused by weak adsorption capacity of isolated single atomic sites to reactants.
[0019] Since ruthenium has a strong ability to dissociate activated hydrogen, the catalyst of the present invention introduces atomically dispersed ruthenium to improve the catalyst's ability to dissociate hydrogen. After hydrogen dissociates at the Ru single atom site, it reacts with the adsorbed and activated acetylene at the adjacent Cu site to generate ethylene. The introduction of a small amount of ruthenium can significantly improve the catalytic performance. If the Ru content is too high, the Ru in the catalyst will aggregate to form clusters, affecting the catalytic activity of the catalyst. The two metals synergistically catalyze the hydrogenation of acetylene, successfully realizing the efficient catalytic selective hydrogenation of acetylene by non-precious metal copper at low temperatures, and the temperature for complete conversion of acetylene is reduced from 200°C required by other copper-based catalysts to 170°C. In addition, the metal loading in the present invention is low, achieving low loading and high catalytic activity, and greatly improving the catalytic efficiency. The low activity of copper in ethylene hydrogenation avoids the occurrence of over-hydrogenation, so that the catalyst maintains high ethylene selectivity when acetylene is completely converted, and the low reaction temperature reduces the generation of coupled polymerization byproducts, which helps to achieve the excellent stability of the catalyst.
[0020] The advantages of the present invention are as follows:
[0021] 1. The present invention designs an atomically dispersed bimetallic catalyst, uses nano-silicon dioxide as a carrier, introduces a small amount of the second component ruthenium, and synergistically catalyzes the acetylene hydrogenation reaction with copper. The metal loading is low, and the metal is atomically dispersed on the surface of the carrier, which is conducive to maximizing the utilization rate of metal atoms. It also has the advantages of a wide range of material sources, environmental friendliness, and mature preparation technology, and has great prospects for industrial application.
[0022] 2. The present invention uses nano-silica-supported ruthenium-copper bimetallic catalyst as an acetylene hydrogenation reaction catalyst. Ruthenium has a strong ability to dissociate and activate hydrogen, which greatly improves the hydrogenation activity of the catalyst. The catalyst exhibits excellent acetylene hydrogenation activity at a relatively low temperature during the acetylene hydrogenation reaction, and has high ethylene selectivity. When the catalyst provided by the present invention catalyzes the acetylene hydrogenation reaction, when the reaction temperature exceeds 170°C, the acetylene conversion rate can reach 100%, and the ethylene selectivity is 90%-100%. The catalyst has excellent stability and can maintain activity for a long time without obvious deactivation.
[0023] 3. The two metals synergistically catalyze the acetylene hydrogenation process, providing an adsorption mode and reaction path that a single metal component does not have, increasing the number of beneficial catalytic active sites, and having the advantage of reducing the competitive adsorption between reactants, thus realizing the low-temperature and efficient catalytic selective hydrogenation of acetylene by non-precious metal copper.
[0024] 4. The catalyst used in the present invention has a mature production process, a simple preparation method, and can be produced on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the transmission electron microscope image of SiO2 carrier;
[0026] Figure 2 The scanning transmission electron micrographs of the catalyst 01Ru05Cu / SiO2 of the present invention are shown in FIG. 1 , wherein: (a) a scanning transmission electron micrograph at a low magnification; (b) a scanning transmission electron micrograph at a high magnification;
[0027] Figure 3 X-ray diffraction spectra of the catalyst 01Ru05Cu / SiO2 and SiO2 carrier of the present invention;
[0028] Figure 4 The acetylene conversion rate and ethylene selectivity of Example 1, Comparative Example 2 and Comparative Example 3 are graphs showing changes with temperature;
[0029] Figure 5 This is a graph showing the stability performance of the catalyst of the present invention in Example 3. DETAILED DESCRIPTION
[0030] The present invention is described in detail below with reference to embodiments.
[0031] The TEM image of the carrier nano-silicon dioxide used in the present invention is as follows: Figure 1 As shown, the particle size statistics show that the average particle size of nano-silicon dioxide is 20nm.
[0032] Example 1
[0033] The preparation process of 01Ru05Cu / SiO2 catalyst in this embodiment is as follows:
[0034] 200 μL of copper nitrate solution (concentration of 0.2 mol / L) was mixed with 20 mL of ammonia solution with a concentration of 5 mol / L, 500 mg of nano-silicon dioxide powder was added thereto, stirred at room temperature for 1 hour, filtered and washed with ultrapure water, the sample was placed in a 60°C vacuum drying oven, taken out after drying, and a nano-silicon dioxide-supported copper catalyst precursor with a copper loading of 0.5 wt% was obtained. 200 μL of hexaammineruthenium chloride solution (concentration of 0.025 mol / L) was mixed with 20 mL of ammonia solution with a concentration of 5 mol / L, 500 mg of the obtained 0.5 wt% nano-silicon dioxide-supported copper catalyst precursor was added thereto, stirred at room temperature for 1 hour, filtered and washed with ultrapure water, the sample was placed in a 60°C vacuum drying oven, taken out after drying, and a nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst precursor with a copper loading of 0.5 wt% and a ruthenium loading of 0.1 wt% was obtained.
[0035] 100 mg of nano-silica-loaded ruthenium-copper bimetallic catalyst precursor was placed in a quartz reaction tube, and a hydrogen-helium mixture (hydrogen gas volume fraction was 10 vol.%) was introduced at a flow rate of 20 mL / min. The mixture was reduced at 300°C for 1 h to obtain a nano-silica-loaded ruthenium-copper bimetallic catalyst with a copper loading of 0.5 wt% and a ruthenium loading of 0.1 wt%, recorded as 01Ru05Cu / SiO2.
[0036] Using spherical aberration corrected high-angle annular dark field-scanning transmission electron microscopy (HAADF-STEM), it can be observed that copper in 01Ru05Cu / SiO2 is dispersed on the carrier surface in the form of clusters and ruthenium is dispersed in the form of single atoms ( Figure 2 ). In the XRD spectrum, only the carrier silica diffraction peak is obvious, and there is no obvious diffraction peak of Cu nanoparticles or Ru nanoparticles, indicating that both Cu and Ru are in a highly dispersed state ( Figure 3 ).
[0037] The catalytic performance of 01Ru05Cu / SiO2 was tested using a fixed bed reactor:
[0038] A mixed raw gas (1% acetylene, 10% hydrogen, 20% ethylene, helium as the balance gas, where the percentages are by volume) was introduced at a space velocity of 6000 mL·g -1 ·h -1 , starting from room temperature, the content of each component at different temperatures was detected by gas chromatography online analysis. The test results are as follows Figure 4 As shown, the acetylene hydrogenation test results show that at 170°C, the acetylene conversion rate is 100% and the ethylene selectivity is 98%.
[0039] Example 2
[0040] The preparation process and conditions of the 01Ru05Cu / SiO2 catalyst in this embodiment are the same as those in Example 1.
[0041] The catalytic performance test process of acetylene hydrogenation is the same as that of Example 1. The difference is that: 100 mg of 01Ru05Cu / SiO2 is heated at a space velocity of 12000 mL·g -1 ·h -1 The catalytic performance test of acetylene hydrogenation was carried out. The results showed that at 200°C, the acetylene conversion rate was 100% and the ethylene selectivity was 91%.
[0042] Example 3
[0043] The preparation process and conditions of the 01Ru05Cu / SiO2 catalyst in this embodiment are the same as those in Example 1.
[0044] This example is a test of catalyst stability. The test process is the same as that of Example 1, except that the reaction temperature is maintained at 165°C. After 25 hours of continuous testing, the catalyst has excellent stability and can maintain long-term activity without obvious deactivation ( Figure 5 ).
[0045] Example 4
[0046] The preparation process of the 02Ru05Cu / SiO2 catalyst in this embodiment is the same as that in Example 1, except that the amount of the hexaammineruthenium chloride solution (concentration of 0.025 mol / L) is 400 μL, and a nano-silica-supported ruthenium-copper bimetallic catalyst with a copper loading of 0.5 wt% and a ruthenium loading of 0.2 wt% is obtained, which is recorded as 02Ru05Cu / SiO2. Copper is dispersed on the surface of the carrier in the form of clusters and ruthenium is dispersed in the form of single atoms.
[0047] The acetylene hydrogenation catalytic performance test process and conditions are the same as in Example 1. The acetylene hydrogenation test results show that at 200°C, the acetylene conversion rate is 100% and the ethylene selectivity is 94%.
[0048] Example 5
[0049] The preparation process of the 002Ru05Cu / SiO2 catalyst in this embodiment is the same as that in Example 1, except that the amount of the hexaammineruthenium chloride solution (concentration of 0.025 mol / L) is 40 μL, and a nano-silica-supported ruthenium-copper bimetallic catalyst with a copper loading of 0.5 wt% and a ruthenium loading of 0.02 wt% is obtained, which is recorded as 002Ru05Cu / SiO2. Copper is dispersed on the surface of the carrier in the form of clusters and ruthenium is dispersed in the form of single atoms.
[0050] The acetylene hydrogenation catalytic performance test process and conditions are the same as in Example 1. The acetylene hydrogenation test results show that at 195°C, the acetylene conversion rate is 100% and the ethylene selectivity is 90%.
[0051] Example 6
[0052] The preparation process of the 005Ru025Cu / SiO2 catalyst in this embodiment is the same as that in Example 1, except that: the amount of copper nitrate solution (concentration of 0.2mol / L) is 100μL, the amount of hexaammineruthenium chloride solution (concentration of 0.025mol / L) is 100μL, and the nano-silica-supported ruthenium-copper bimetallic catalyst with a copper loading of 0.25wt% and a ruthenium loading of 0.05wt% is obtained, which is recorded as 005Ru025Cu / SiO2. Copper is dispersed on the carrier surface in the form of clusters and ruthenium is dispersed in the form of single atoms.
[0053] The catalytic performance test process of acetylene hydrogenation is the same as that of Example 1. The difference is that: 100 mg of 005Ru025Cu / SiO2 is heated at a space velocity of 3000 mL·g -1 ·h -1 The acetylene hydrogenation catalytic performance test was carried out at the same time. The acetylene hydrogenation test results showed that the acetylene conversion rate was 100% and the ethylene selectivity was 96% at 210°C.
[0054] Example 7
[0055] The reduction process of the 01Ru05Cu / SiO2 catalyst in this embodiment is different from that in Example 1 in that a hydrogen-helium mixed gas (hydrogen gas volume fraction is 99 vol.%) is introduced at a flow rate of 20 mL / min and the reduction is carried out at 300°C for 30 min. The acetylene hydrogenation catalytic performance test process is the same as in Example 1, with a space velocity of 6000 mL·g -1 ·h -1 The results showed that at 170°C, the acetylene conversion was 100% and the ethylene selectivity was 97%.
[0056] Comparative Example 1
[0057] The preparation process of the 05Ru05Cu / SiO2 catalyst in this comparative example is the same as that in Example 1, except that the amount of the hexaammineruthenium chloride solution (concentration of 0.025 mol / L) is 1 mL, and a nano-silica-supported ruthenium-copper bimetallic catalyst with a copper loading of 0.5 wt% and a ruthenium loading of 0.5 wt% is obtained, which is recorded as 05Ru05Cu / SiO2. Copper is dispersed on the surface of the carrier in the form of clusters and ruthenium is dispersed in the form of clusters.
[0058] The acetylene hydrogenation catalytic performance test process and conditions are the same as in Example 1. The acetylene hydrogenation test results show that at 200°C, the acetylene conversion rate is 65% and the ethylene selectivity is 100%. The results show that if Ru aggregates on the support surface to form clusters, the dispersion degree decreases, which in turn leads to a decrease in catalytic performance. At the same temperature as in Example 1, the acetylene conversion rate decreases, and even if the reaction temperature is increased to 200 degrees, acetylene cannot be completely converted, indicating that the high dispersion of Ru atoms in the RuCu bimetallic acetylene hydrogenation catalyst plays an important role in obtaining high hydrogenation activity of the catalyst at low temperatures.
[0059] Comparative Example 2
[0060] The preparation process of 05Cu / SiO2 catalyst in this comparative example is as follows:
[0061] 100 mg of the nano-silicon dioxide-supported copper catalyst precursor with a copper loading of 0.5 wt% obtained in Example 1 was placed in a quartz reaction tube, and the reduction process and conditions were the same as in Example 1. That is, a nano-silicon dioxide-supported copper catalyst with a copper loading of 0.5 wt% was obtained, which was recorded as 05Cu / SiO2.
[0062] The acetylene hydrogenation catalytic performance test process and conditions are the same as in Example 1. The results are as follows Figure 4 As shown, the acetylene hydrogenation test results show that at 200°C, the acetylene conversion rate is 13% and the ethylene selectivity is 100%.
[0063] By comparison, the hydrogenation activity of the single metal Cu catalyst prepared under the same conditions is much lower than that of the bimetallic RuCu catalyst, and it still shows poor ability to activate hydrogen even at high reaction temperatures. However, the addition of Ru to the bimetallic catalyst significantly enhances the acetylene hydrogenation activity of the catalyst, greatly reducing the temperature for complete conversion of acetylene, and achieving the goal of designing a low-temperature and efficient acetylene selective hydrogenation catalyst.
[0064] Comparative Example 3
[0065] The preparation process of 01Ru / SiO2 catalyst in this comparative example is as follows:
[0066] 200 μL of hexaammineruthenium chloride solution (concentration of 0.025 mol / L) was mixed with 20 mL of 5 mol / L ammonia solution, 500 mg of nano-silica powder was added thereto, stirred at room temperature for 1 hour, filtered and washed with ultrapure water, and the sample was placed in a 60°C vacuum drying oven, dried and taken out to obtain a nano-silica supported ruthenium catalyst precursor with a ruthenium loading of 0.1 wt%; 100 mg of the obtained nano-silica supported ruthenium catalyst precursor with a ruthenium loading of 0.1 wt% was placed in a quartz reaction tube, and the reduction process and conditions were the same as in Example 1. That is, a nano-silica supported ruthenium catalyst with a ruthenium loading of 0.1 wt% was obtained, recorded as 01Ru / SiO2.
[0067] The acetylene hydrogenation catalytic performance test process and conditions are the same as in Example 1. The acetylene hydrogenation test results are as follows Figure 4 As shown, the single metal Ru catalyst has almost no activity for acetylene hydrogenation. Compared with the bimetallic catalyst, it shows that Cu is the key site for adsorbing and activating acetylene.
[0068] The nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst prepared by the method of the present invention realizes low-temperature and efficient selective hydrogenation of acetylene, maintains high ethylene selectivity when acetylene is fully converted, and has excellent catalyst stability. By introducing the second component metal ruthenium, beneficial active sites are increased, and the ability of the catalyst to activate and dissociate hydrogen and adsorb and activate acetylene is improved. The two metals synergistically improve the catalytic performance of acetylene hydrogenation, and its performance is much higher than that of a single-component ruthenium or copper catalyst under the same conditions. Moreover, ruthenium and copper are atomically dispersed on the surface of the silica carrier, which is conducive to maximizing the utilization rate of metal atoms, and the metal loading is low. Compared with the traditional palladium-silver alloy catalyst, the catalyst cost is greatly reduced, and the catalyst synthesis method is mature, the preparation process is convenient and easy to implement, and it is environmentally friendly.
[0069] The above are preferred embodiments of the present invention, but the protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are also included in the present invention.
Claims
1. A nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst, characterized in that: The catalyst uses nano-silicon dioxide as a carrier; copper and ruthenium are used as active materials, copper is dispersed and anchored on the carrier surface in the form of clusters and ruthenium is dispersed and anchored in the form of single atoms; the copper loading in the catalyst is 0.1wt.% to 2wt.% of the carrier mass, and the ruthenium loading is 0.02wt.% to 0.5wt.% of the carrier mass; During the acetylene hydrogenation reaction, when the reaction temperature exceeds 170° C., the acetylene conversion rate reaches 100% and the ethylene selectivity is 90%-100%.
2. The nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst according to claim 1, characterized in that: The loading amount of copper is 0.25wt.% to 1wt.% of the carrier mass; the loading amount of ruthenium is 0.05wt.% to 0.2wt.% of the carrier mass.
3. A method for preparing the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst according to claim 1 or 2, characterized in that: The following steps are involved: Step 1. Preparation of nano-silica supported copper catalyst precursor by strong electrostatic adsorption method Weighing a Cu precursor and dissolving it in an ammonia solution to obtain a mixed solution; adding a nano-silica carrier to the mixed solution, stirring at room temperature to react, and then filtering, washing, and vacuum drying to obtain a nano-silica-supported copper catalyst precursor; Step 2. Preparation of nano-silica-supported ruthenium-copper bimetallic catalyst precursor by strong electrostatic adsorption method Weighing a Ru precursor and dissolving it in an ammonia solution to obtain a mixed solution; adding a nano-silica-supported copper catalyst precursor to the mixed solution, stirring at room temperature, and obtaining a nano-silica-supported ruthenium-copper bimetallic catalyst precursor after suction filtration, washing, and vacuum drying; Step 3. Preparation of nano-silica supported ruthenium-copper bimetallic catalyst by reduction treatment The nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst precursor is reduced in a hydrogen-helium mixed atmosphere to obtain the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst.
4. The method for preparing the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst according to claim 3, characterized in that: In step 1, the molar ratio of NH3 to Cu in the mixed solution is NH3:Cu>20:1; the Cu precursor is copper nitrate; the average particle size of nano-silicon dioxide is 20nm, and the mass ratio of the carrier to copper is (50-1000):1; the reaction time is 2h-12h, the stirring rate is 300r / min-900r / min; and the drying temperature is 60℃-80℃.
5. The method for preparing the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst according to claim 3, characterized in that: In step 2, the Ru precursor is hexaammineruthenium chloride; the molar ratio of NH3 and Ru in the mixed solution is NH3:Ru>20:1; the mass ratio of the added amount of nano-silica-supported copper catalyst precursor to Ru is (200-5000):1; the stirring time is 2h-12h, the stirring rate is 300r / min-900r / min; and the drying temperature is 60℃-80℃.
6. The method for preparing the nano-silicon dioxide-supported ruthenium-copper bimetallic catalyst according to claim 3, characterized in that: In step 3, the volume fraction of hydrogen gas in the hydrogen-helium mixture is 10 vol.%-100 vol.%, the flow rate is 20 mL / min-100 mL / min; the reduction temperature is 250° C.-350° C., and the reduction time is 0.5 h-2 h.
7. The nano-silica supported ruthenium copper bimetallic catalyst according to claim 1 or 2 is used in acetylene hydrogenation reaction, characterized in that: The catalyst catalyzes the selective hydrogenation of acetylene in the mixed raw gas to produce ethylene.
8. The nano-silica supported ruthenium copper bimetallic catalyst according to claim 7 is used in acetylene hydrogenation reaction, characterized in that: The composition of the mixed raw gas is calculated by volume fraction: acetylene 0.5vol.%-1vol.%, hydrogen 5vol.%-10vol.%, ethylene 10vol.%-20vol.%, helium as the balance gas; the space velocity is 2000-60000mL·g -1 ·h -1 .
Citation Information
Cited By
Catalyst for preparing 1, 4-cyclohexanedimethanol by catalyzing dimethyl terephthalate hydrogenation one-pot method and preparation method thereof
CN120571586A
Nanoscale high-dispersity rhenium-based catalyst for preparing perfluorobutyl ethylene as well as preparation method and application of nanoscale high-dispersity rhenium-based catalyst
CN121402078A
A nanoscale highly dispersed rhenium-based catalyst for the preparation of perfluorobutylethylene, its preparation method and application
CN121402078B